(untitled) (CIPEEX, 2026)
ABSTRACT Context: This work aims to analyze Environmental Education through the concept of the Pedagogy of the Apocalypse, a term that has emerged in recent years in light of the environmental crisis and the resulting eco-anxiety. Problematization: Environmental Education as a Pedagogy of the Apocalypse seeks to understand and encourage students to develop a critical awareness in the face of catastrophic scenarios, the exploitation of natural resources for the sake of excessive consumption, and the accumulation of wealth. Objective: The research challenge is to understand the present and future impacts of climate change, thus considering the causes and means to adapt to these transformations. Methodology: This work consists of a study based on a deductive and bibliographical approach, conducted through a review and analysis of the literature with an interpretative objective. The instruments that will be used for the bibliographic research consist of books, scientific articles, theses, and dissertations that have already been published. Result: The expected outcomes of this work are: to broaden the discussion on the concept of Pedagogy of the Apocalypse in the context of environmental education; to present the impact of Pedagogy of the Apocalypse on informal environmental education presented in the media and its potential in formal education. Conclusion: Therefore, Pedagogy of the Apocalypse aims to reflect on the world and encourage speculation for critical thinking in the face of climate change and the disruptive changes that come with modernity. In other words, it presents the idea that we need to be encouraged to rethink in a world with new attitudes and ways of intervening.